2023
DOI: 10.3389/fphar.2023.1062290
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication including drug-drug interaction and the risk of frequent falling, hospital admission, and death in older adults - results of a large cohort study (getABI)

Abstract: Introduction: With growing age, multiple chronic diseases may result in polypharmacy. Drugs that should be avoided in older adults are called potentially inappropriate medications (PIM). Beyond PIM, drug-drug interactions (DDI) are known to be related to adverse drug events. This analysis examines the risk of frequent falling, hospital admission, and death in older adults associated with PIM and/or DDI (PIM/DDI) prescription.Materials and methods: This post hoc analysis used data of a subgroup of the getABI st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…The results showed a high prevalence of HRP in all patients, with a mean of 8.22 prescribed drugs per patient. This is similar to other studies in Europe ( Pasina et al, 2020 ; Reinhild Haerig et al, 2023 ). More than 80% of the patients received recommendations, and for 50%, at least one drug was recommended to be withdrawn due to MRPs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed a high prevalence of HRP in all patients, with a mean of 8.22 prescribed drugs per patient. This is similar to other studies in Europe ( Pasina et al, 2020 ; Reinhild Haerig et al, 2023 ). More than 80% of the patients received recommendations, and for 50%, at least one drug was recommended to be withdrawn due to MRPs.…”
Section: Discussionsupporting
confidence: 93%
“…Increased exposure to complex drug regimens involving ≥5 drugs, known as polypharmacy, or excessive polypharmacy, as in patients treated with 10 or more medications concomitantly, raises the risk of adverse events ( Stuhec et al, 2021 ). Polypharmacy can also affect drug safety due to potentially inappropriate medications (PIMs), adverse drug reactions (ADRs), and the risk of interactions ( Burato et al, 2021 ; Zhang et al, 2022 ; Doumat et al, 2023 ; Reinhild Haerig et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed the associations between DDI-PIM and hospitalization in NH residents. However, a previous study reported the risk of hospitalization were increased in community-dwelling older adults exposed to DDI-PIM, including concurrent use of antiplatelets and NSAIDs without PPI, multiple antiplatelets without PPI, antiplatelets plus oral anticoagulants without PPI, and ACE inhibitors/ARB with NSAID [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators recently conducted a retrospective analysis to evaluate the association between risk of frequent falling, hospitalization, and mortality in older adults with PIM and/or DDI (Haerig et al, 2023).…”
Section: Y W Francis Lam Pharmd Fccpmentioning
confidence: 99%